Dirhodium(II)-catalyzed [3 + 2] cycloaddition of N-arylaminocyclopropane with alkyne derivatives - Liu, Wentong; Kuang, Yi; Wang, Zhifan; Zhu, Jin; Wang, Yuanhua (Beilstein Journal of Organic Chemistry, 2019)
Dirhodium(II) complex-catalyzed [3 + 2] reactions between N-arylaminocyclopropanes and alkyne derivatives are described. The cycloaddition products proved to be versatile synthetic intermediates. trans-Cyclic β-amino acids and derivatives thereof can be conveniently synthesized using this cycloaddition protocol.
Keywords: [3 + 2]; alkyne; cycloaddition; cyclopropanes; dirhodium catalysis; N-arylaminocyclopropanes